ANALISIS KONTRIBUSI INSTRUMEN INVESTASI SYARIAH MELIPUTI SUKUK DAN REKSADANA SYARIAH DALAM MENDUKUNG PERTUMBUHAN EKONOMI BERKELANJUTAN DI NEGARA-NEGARA MUSLIM BERKEMBANG - Haridah, Haridah (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
Sustainable economic growth is a critical agenda for developing Muslim countries facing the challenges of globalization and climate change. Islamic investment instruments such as sukuk and Islamic mutual funds provide an alternative financing mechanism aligned with Sharia principles, promoting inclusive and sustainable development. This study aims to analyze the contribution of these Islamic investment instruments to sustainable economic growth in developing Muslim countries. Utilizing panel data from 20 member countries of the Organization of Islamic Cooperation (OIC) over the period 2020–2025, this study applies fixed-effect panel regression analysis. The dependent variable is a sustainable economic growth index incorporating economic, social, and environmental dimensions. Independent variables include sukuk issuance and Islamic mutual fund assets under management, with control variables covering Islamic financial literacy, inflation, and conventional interest rates. The findings reveal that both sukuk issuance and Islamic mutual funds significantly and positively impact sustainable economic growth, with sukuk having the most substantial effect. Moreover, Islamic financial literacy enhances the positive relationship between Islamic investment instruments and sustainable growth. The study underscores the necessity of strengthening regulations, transparency, and Islamic financial education to accelerate the development of Islamic capital markets that contribute to sustainable development. Policy implications include enhancing Islamic financial literacy programs, developing green investment products, and fostering multi-stakeholder collaboration to build an inclusive and sustainable Islamic investment ecosystem. These findings provide robust empirical evidence for policymakers and Islamic capital market participants to optimize the role of Islamic investment instruments as pillars of sustainable economic development in developing Muslim countries.